Amiloidosi da transtiretina (ATTR): l'altra faccia della medaglia - Federico Perfetto; Francesco Cappelli; Silvia Farsetti; Elio Dimarcantonio; Silvia Casagrande; Massimo Di Gioia; Marco Di Girolamo; Franco Bergesio (AboutScience Srl, 2019)
Transthyretin amyloidosis (ATTR) is becoming an emerging clinical entity, and is currently the most common form of systemic amyloidosis. ATTR consists of two distinct diseases depending on whether the amyloid fibrils derive from the intact molecule of TTR (ATTR wild-type or senile systemic amyloidosis) or from different mutations occurred in the TTR molecule gene (ATTRm). Total-body scintigraphy with diphosphonates has greatly improved the diagnosis in patients with isolated cardiac involvement for both ATTRm and ATTRwt, thus avoiding the need of endomiocardial biopsy in cases without serum and/or urinary monoclonal component (MC). Heart failure alone, or associated with peripheral and autonomic neuropathy, are the main clinical symptoms in these patients. Particular attention must be paid in order to exclude hypertrophic cardiomiopathy or light chain (AL) forms in patients with MC. Today, besides hepatic transplantation, which is almost reserved to patients with early Val30Met neuropathy, many new therapeutic alternatives can be offered to these patients. Tafamidis, a TTR-stabilizer that has recently proved to be effective in cardiac forms of both ATTRm and ATTRwt, is now ready for clinical use. In addition, drugs silencing the TTR messenger RNA should soon be available for treatment. The many therapeutic opportunities available today for ATTR, strenghten even more the need for an early diagnosis of the disease both in ATTRm and ATTRwt.